ECG Signal Feature Extraction and Classification: Survey - Bhirud, Bhagyashri; Pachghare, Vinod (International Journal of Computer Sciences and Engineering, 2025)
Nowadays due to busy and hectic lifestyle, many people cannot pay enough attention to their health. Stress, junk food, obesity, smoking and lack of exercise leads to heart diseases. It is one of major cause leading rise to death rate. ECG (Electrocardiogram) is the best and easiest way to record and analyze the electrical and muscular activities of heart. Due to nonlinearity and complexity of ECG signals, it requires significant amount of training to analyze and study the ECG waveform. For preventive measures and predictive analysis, it is necessary to analyze these waveforms in faster, efficient way and in real time too. Number of methods and techniques have been developed in recent time. Different techniques and methodologies are discussed in this literature review.